Reproduction in Farm Animals (Lea & Febiger, 2000)
When you're looking for a comprehensive and reliable text on large animal reproduction, look no further! the seventh edition of this classic text is geared for the undergraduate student in Agricultural Sciences and Veterinary Medicine.